Operando visualisation and multi-scale tomography studies of dendrite formation and dissolution in zinc batteries - Yufit,V; Tariq,F; Biton,M; Brandon,N (Joule, 2019)
Alternative battery technologies are required to meet growing energy demands and address the limitations of present technologies. As such, it is necessary to look beyond lithium-ion batteries. Zinc batteries enable high power density while being sourced from ubiquitous and cost-effective materials. This paper presents, for the first time known to the authors, multi-length scale tomography studies of failure mechanisms in zinc batteries with and without commercial microporous separators. In both cases, dendrites were grown, dissolved, and regrown, critically resulting in different morphology of dendritic layer formed on both the electrode and the separator. The growth of dendrites and their volume-specific areas were quantified using tomography and radiography data in unprecedented resolution. High-resolution ex situ analysis was employed to characterize single dendrites and dendritic deposits inside the separator. The findings provide unique insights into mechanisms of metal-battery failure effected by growing dendrites.